1989
DOI: 10.1007/bf02840596
|View full text |Cite
|
Sign up to set email alerts
|

Metal complexes of thymidine — a study of binary and ternary systems with bivalent and trivalent metal ions in solution

Abstract: The interaction of bivalent I-Cu(II), Ni(II), Zn(II), Co(II), Mg(II), Ca(II)] and trivalent I-La(III), Pr(III), Nd(III), Sm(III), Gd(llI), Dy(IIl)] metal ions with thymidine both in binary and ternary systems have been investigated by potentiometric pH measurements at 35~ and 0-10 M (KNO2) ionic strength. The secondary ligands used in this investigation were glycine, histidine, histamine, o-phenanthroline and a, ~,'-bipyridyl. The various stability constants pertaining to the above interactions were computed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Choppin et al studied lanthanide complexation by benzoic acid and isophthalic acid and suggested that in the latter ligand, steric effects prevent simultaneous binding to both carboxylate sites. Studies on complex formation by tripositive rare earth ions with biologically important ligands are in progress because of their role in biochemical processes, and some lanthanide complexes with nucleosides/nucleotides are also available in the literature. To the best of our knowledge, no examples of the interaction of uracil and its halo derivatives with lanthanides in the presence of benzoic acid/its derivatives are known to date. The present paper reports studies on the interaction of uracil (Ur), 5-fluorouracil (FUr), 5-chlorouracil (ClUr), and 5-bromouracil (BrUr) as one ligand and benzoic acid (OBz), 4-nitrobenzoic acid (NBz), 4-fluorobenzoic acid (FBz), 4-chlorobenzoic acid (ClBz), and 4-bromobenzoic acid (BrBz) as another ligand with Eu(III), Gd(III), and Tb(III) in 1:1:1 ratio potentiometrically at (25 ± 0.1) °C.…”
Section: Introductionmentioning
confidence: 99%
“…Choppin et al studied lanthanide complexation by benzoic acid and isophthalic acid and suggested that in the latter ligand, steric effects prevent simultaneous binding to both carboxylate sites. Studies on complex formation by tripositive rare earth ions with biologically important ligands are in progress because of their role in biochemical processes, and some lanthanide complexes with nucleosides/nucleotides are also available in the literature. To the best of our knowledge, no examples of the interaction of uracil and its halo derivatives with lanthanides in the presence of benzoic acid/its derivatives are known to date. The present paper reports studies on the interaction of uracil (Ur), 5-fluorouracil (FUr), 5-chlorouracil (ClUr), and 5-bromouracil (BrUr) as one ligand and benzoic acid (OBz), 4-nitrobenzoic acid (NBz), 4-fluorobenzoic acid (FBz), 4-chlorobenzoic acid (ClBz), and 4-bromobenzoic acid (BrBz) as another ligand with Eu(III), Gd(III), and Tb(III) in 1:1:1 ratio potentiometrically at (25 ± 0.1) °C.…”
Section: Introductionmentioning
confidence: 99%